FLUORIMETRIC DETECTIONS OF OIL SEEPS ON THE SEA FLOOR - Karabashev G.S.; Khanayev S.A. (My University, 1989)
The possibility of fluorimetric detection of oil seeps on the sea floor has often been raised since the late 1950's, because many natural hydrocarbons, including petroleum fractions, fluoresce brightly under UV illumination, and fluorimetric measurements are highly sensitive and can detect extremely low concentrations of such substances. Sea water also contains endogene fluorescing compounds (dissolved organic matter: DOM), whose fluorescence is similar to that of petroleum and thus interferes with fluorimetric detection of the latter. It is better to take the direct approach of investigating water bodies where seepage of hydrocarbons into the water from the bottom either is known to occur or is probable. We undertook such an investigation in July and August of 1987 in the northern part of the Gdansk Basin of the Baltic Sea, where oil fields have been found and where methane accumulations occur in the top layer of sediments in certain limited areas as a result of gas migration from deeper layers. We attempted to obtain data on the distribution of UV-induced fluorescence in the bottom water of this area. The main difference in the vertical fluorescence profile of the bottom layer and the temperature and turbidity (i.e., scattering) profiles was that the equal-fluorescence lines on the traverses predominantly followed the bottom relief, while the isotherms and equal-turbidity contours were largely horizontal. This difference showed up most clearly on traverses where the depth changed smoothly.